Madrasah Quality Improvement Management - Sita Ratnaningsih; Maftuhah; Taufiqurrahman (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
One factor that greatly influences the success of a school is educational resources, excellent educational resources are produced by good quality management. Quality is very important in an educational institution, schools are said to be superior and able to compete if management is good. The purpose of this research is to provide understanding and insight regarding education quality management and educational assistance at MTs Darut Tafsir Al-Husaini. The result of this service activity is to improve the quality of madrasas to be even better so that madrasas have the potential to become superior and competitive madrasas.